An Analysis of the Causes of Suicide in Japan and the Government's Efforts in Overcoming Them: Analisis Penyebab Kasus Bunuh Diri di Jepang dan Upaya Pemerintah Dalam Mengatasinya - Naila Hanifa Nurazkia; Astri Aulia; Wulan Nanda Asyifa; Zahra Kamilla Baswandana Basri; Dewanty, Via Luviana; Hamidah, Siti (Undiksha Press, 2025)
The surge in suicide cases in Japan has recently captured public attention. This article delves into the causes, consequences, and government efforts to address these cases. Employing a Systematic Literature Review methodology, this study identifies the factors influencing the rise in suicide cases in Japan and evaluates the effectiveness of government policies implemented. The research reveals that the Japanese face complex social pressures, particularly due to high levels of individualism and a lack of social support. This study provides a foundational knowledge base to facilitate further analysis and assist the government in taking more effective actions to reduce suicide rates in Japan.